Kadar Bilirubin, Alkalin Fosfatase, dan Gamma Glutamil Transpeptidase Serum sebagai Prediktor Batu Duktus Koledokus pada Pasien Batu Empedu Simtomatik - Kaunang, Maria; Panelewen, Jimmy; Mambu, Toar (UNIVERSITAS SAM RATULANGI, 2019)
Abstract: Complications of the common bile duct stone occur in 10-15% of patients with gallstones. Bilirubin, alkaline phosphatase (ALP), and gamma glutamyl transpeptidase (GGT) are routine laboratory tests performed on patients with gallstones. This study was aimed to determine whether bilirubin, ALP, and GGT serum could be used as predictors of common bile duct stone in patient with symptomatic gallstone at Prof. Dr. R. D. Kandou Hospital Manado and its satellite hospitals. This was a prospective analytical observational study with a cross sectional design. Subjects were 38 patients with symptomatic gallstone that underwent definitive surgery. The bilirubin, ALP, and GGT serum levels were taken at presentation. Receiver operating character-istic curve analysis was used to determine optimal biochemical cut-off value of each parameter. The results showed that of 38 patients, 22 patients were male and 16 patients were female. The mean ages were 52 years in males and 47 years in females. There were 28 patients proven to have stones in common bile ducts. All parameters were proven to be effective in predicting common bile duct stone, as follows: bilirubin cut-off point was 1.6 U/L with sensitivity of 96.4% and specifity of 90%; ALP cut-off point was 114 U/L with sensitivity of 82.1% and specifity of 90%; and GGT cut-off point was 102.5 U/L with sensitivity of 85.7% and specifity of 90%. Conclusion: Bilirubin, ALP, and GGT serum levels can be used as predictors of common bile duct stone in patient with symptomatic gallstone.Keywords: bilirubin, ALP, GGT, common bile duct stoneAbstrak: Komplikasi batu duktus koledokus terjadi pada 10-15% pasien dengan batu empedu. Bilirubin, alkalin fosfatase (ALP), and gamma glutamil transpeptidase (GGT) merupakan pemerik-saan laboratorium rutin pada pasien dengan batu empedu. Penelitian ini bertujuan untuk menentukan apakah bilirubin, ALP, dan GGT serum dapat dipakai sebagai prediktor batu duktus koledokus pada pasien dengan batu empedu simtomatik di RSUP Prof. Dr. R. D. Kandou Manado dan rumah sakit jejaringnya. Jenis penelitian ialah observasional analitik prospektif dengan desain potong lintang. Pemeriksaan kadar bilirubin, ALP, dan GGT serum dilakukan pada semua subyek saat didiagnosis batu empedu simtomatik. Receiver operating characteristic curve analysis diguna-kan untuk menentukan nilai titik potong biokimia yang optimal dari setiap parameter. Hasil penelitian mendapatkan sebanyak 38 pasien dengan batu empedu simtomatik yang menjalani operasi definitif, terdiri dari 22 pasien laki-laki and 16 pasien perempuan. Rerata usia subyek ialah 52 tahun pada laki-laki dan 47 tahun pada perempuan. Terdapat 28 pasien terbukti dengan batu duktus koledokus. Semua parameter terbukti efektif dalam memrediksi batu doktus koledokus sebagai berikut: titik potong bilirubin serum 1,6 U/L dengan sensitivitas 96,4% and spesifitas 90%; titik potong ALP serum 114 U/L dengan sensitivitas 82,1% dan spesifitas 90%; titik potong GGT serum 102,5 U/L dengan sensitivitas 85,7% dan spesifitas 90%. Simpulan: Kadar bilirubin, ALP, dan GGT serum dapat dipakai sebagai prediktor batu duktus koledokus pada pasien dengan batu empedu simtomatik.Keywords: bilirubin, ALP, GGT, batu duktus koledokus